KONTRIBUSI KOMUNIKASI ASERTIF DAN KEPEMIMPINAN DALAM UPAYA MENINGKATKAN PRODUKTIVITAS KERJA: KAJIAN LITERATUR - Syifaa Freza Aprilistyan; Khairul Ikhwan (Transpublika Publisher, 2022)
Productivity is a very important factor for employees to consider in a company. The working conditions experienced by employees have a significant impact on the amount of work produced. Work productivity shows the level of workforce ability in achieving an output. This study aims to determine the contribution of assertive communication and leadership to work productivity. This study uses a literature review method using secondary data. Secondary data in this study were obtained from previous studies published in accredited national journals over the last ten years. Based on the results of the literature review, it is found that assertive communication and leadership in general have a significant effect on increasing work productivity.